1999
DOI: 10.1038/sj.onc.1202702
|View full text |Cite
|
Sign up to set email alerts
|

JNK activation is not required for Fas-mediated apoptosis

Abstract: Fas ligation in the presence of cycloheximide induced Jun N-terminal kinase 1 (JNK1) and JNK2 phosphorylation, caspase activation and cell death in the IL-3-dependent cell line BAF3. Fas-mediated apoptosis was prevented by expression of dominant negative FADD but not inhibited by IL-3. To investigate the role of JNK activation in this process, we examined cells overexpressing a JNK-speci®c phosphatase M3/6. M3/6 prevented Fas stimulation of JNK, but did not a ect Fas-mediated caspase activation or cell death, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…6C), demonstrating the efficacy of this JNK inhibitor. These results show that JNK is not required for CCN1/FasL synergism, in concordance with previous findings that JNK is dispensable for Fas-mediated apoptosis in lymphocytes (44). By contrast, the chemical blockers SB202190 and SB203580, which inhibit both p38␣ and p38␤ isoforms, significantly diminished FasL/CCN1-induced apoptosis (Fig.…”
Section: Ccn1 and Ccn2 Synergize With Fasl To Induce Apoptosissupporting
confidence: 81%
“…6C), demonstrating the efficacy of this JNK inhibitor. These results show that JNK is not required for CCN1/FasL synergism, in concordance with previous findings that JNK is dispensable for Fas-mediated apoptosis in lymphocytes (44). By contrast, the chemical blockers SB202190 and SB203580, which inhibit both p38␣ and p38␤ isoforms, significantly diminished FasL/CCN1-induced apoptosis (Fig.…”
Section: Ccn1 and Ccn2 Synergize With Fasl To Induce Apoptosissupporting
confidence: 81%
“…128 FAS-induced activation of the Jnk pathway is reported to require caspase activation, 129 however, in the IL-3-dependent cell line BAF-3, over-expression of a Jnk specific phosphatase (M3/6) did not effect FAS-mediated apoptosis. 130 These data support the idea that FAS-induced apoptosis may lead to the induction of Jnk activation, but this activation is not required for FAS-induced apoptosis of hematopoietic cells. In contrast to these findings it was reported, using a dominant-negative Jnk, that Jnk activation is required for apoptosis induced by the Rho family member CDC42.…”
Section: The Stress-activated Protein Kinasessupporting
confidence: 77%
“…JNK activation has been reported to accompany Fas receptor activation. Some studies found that JNK was not required for Fas receptor-mediated apoptosis (Abreu-Martin et al, 1999;Low et al, 1999;Hofmann et al, 2001), but others have shown that JNK activation accelerates Fas-mediated apoptosis in a number of cell lines (Brenner et al, 1997;Yang et al, 1997;Le-Niculescu et al, 1999;Zhang et al, 2000). Our group has previously identified JNK activation as being necessary for Fas-mediated apoptosis in DU 145 cells (CostaPereira et al, 2000;Curtin and Cotter, 2002).…”
Section: Du 145 Prostate Carcinoma Cells Are Resistant To Fas-mediatementioning
confidence: 99%